Melody Processing Characterizes Functional Neuroanatomy in the Aging Brain - Agustus, Jennifer L.; Golden, Hannah L.; Callaghan, Martina F.; Bond, Rebecca L.; Benhamou, Elia; Hailstone, Julia C.; Weiskopf, Nikolaus; Warren, Jason D. (Frontiers in Neuroscience, 2018)
The functional neuroanatomical mechanisms underpinning cognition in the normal older brain remain poorly defined, but have important implications for understanding the neurobiology of ageing and the impact of neurodegenerative diseases. Auditory processing is an attractive model system for addressing these issues. Here we used fMRI of melody processing to investigate auditory pattern processing in normal older individuals. We manipulated the temporal (rhythmic) structure and familiarity of melodies in a passive listening, ‘sparse’ fMRI protocol. A distributed cortico-subcortical network was activated by auditory stimulation compared with silence; and within this network, we identified separable signatures of anisochrony processing in bilateral posterior superior temporal lobes; melodic familiarity in bilateral anterior temporal and inferior frontal cortices; and melodic novelty in bilateral temporal and left parietal cortices. Left planum temporale emerged as a ‘hub’ region functionally partitioned for processing different melody dimensions. Activation of Heschl’s gyrus by auditory stimulation correlated with the integrity of underlying cortical tissue architecture, measured using multi-parameter mapping. Our findings delineate neural substrates for analysing perceptual and semantic properties of melodies in normal ageing. Melody (auditory pattern) processing may be a useful candidate paradigm for assessing cerebral networks in the older brain and potentially, in neurodegenerative diseases of later life.